(3eHGOF aj GdYdGbGJ GdYGeI (B/s - (3GdTQeGf, RjGO eMeOs; (3YHO GdSdGe, YHO GdZahQ YHO Gddg s ((3HjQhJ(B: s (3OGQ UaGA ddfTQ(B, s, 2001)
(3eHGOF aj GdYdGbGJ GdYGeI,JfXje EOGQI GdYdGbGJ GdYGeI,GdhUa GdJhXjaj ddYGedjf aj GdYdGbGJ GdYGeI,GdGJUGdGJ GdGOGQjI,hSGFd GdGJUGd,GdYdGbGJ GdYGeI hGdLeghQ GdOGNdj aj GdefXeI,GdYdGbGJ GdYGeI hGdLeghQ GdNGQLj ddefXeI,fTGWGJ GdYdGbGJ GdYGeI,JUeje HQfGeL GdYdGbGJ GdYGeI hJbjjeg,GdQCj GdYGe,GdYdGbGJ GdYGeI aj GdbWGYjf GdYGe hGdNGUs
(3HHdjhZQGajG(B:(3U(B.191s
Keywords: (3GdGJUGd GdLeGgjQjs; (3GdYdGbGJ GdYGeIs